2021
DOI: 10.3389/fimmu.2021.717157
|View full text |Cite
|
Sign up to set email alerts
|

Kynurenic Acid and Its Synthetic Derivatives Protect Against Sepsis-Associated Neutrophil Activation and Brain Mitochondrial Dysfunction in Rats

Abstract: Background and AimsThe systemic host response in sepsis is frequently accompanied by central nervous system (CNS) dysfunction. Evidence suggests that excessive formation of neutrophil extracellular traps (NETs) can increase the permeability of the blood–brain barrier (BBB) and that the evolving mitochondrial damage may contribute to the pathogenesis of sepsis-associated encephalopathy. Kynurenic acid (KYNA), a metabolite of tryptophan catabolism, exerts pleiotropic cell-protective effects under pro-inflammator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 59 publications
0
18
0
Order By: Relevance
“…KYNA and SZR104 not only attenuated tumor necrosis factor-α (TNF-α) production and increased tumor necrosis factor-stimulated gene-6 mRNA expression in U-937 cells stimulated with heat-inactivated Staphylococcus aureus [8] but they also inhibited the LPS-stimulated phagocytotic activity of microglial cells in vitro while suppressing microglial activity in an in vivo model of epilepsy [5]. Another potent proinflammatory citokine, interleukin-1β, was elevated in sepsis but was ameliorated by KYNA and its synthetic analogues SZR72 and SZR104 [44]. Furthermore, SZR72 inhibited the production of the inflammatory mediators TNF-α, calprotectin, S100A12, and HNP1-3 in blood cultures of rheumatoid arthritis patients [45].…”
Section: Discussionmentioning
confidence: 99%
“…KYNA and SZR104 not only attenuated tumor necrosis factor-α (TNF-α) production and increased tumor necrosis factor-stimulated gene-6 mRNA expression in U-937 cells stimulated with heat-inactivated Staphylococcus aureus [8] but they also inhibited the LPS-stimulated phagocytotic activity of microglial cells in vitro while suppressing microglial activity in an in vivo model of epilepsy [5]. Another potent proinflammatory citokine, interleukin-1β, was elevated in sepsis but was ameliorated by KYNA and its synthetic analogues SZR72 and SZR104 [44]. Furthermore, SZR72 inhibited the production of the inflammatory mediators TNF-α, calprotectin, S100A12, and HNP1-3 in blood cultures of rheumatoid arthritis patients [45].…”
Section: Discussionmentioning
confidence: 99%
“…Moroni et al (2012) were the first to communicate that KYNA administered subcutaneously at doses of 500 mg/kg (single injection) or 200 mg/kg three times at 0, 3, and 6 h after LPS dramatically reduced LPS-induced death in mice [ 98 ]. The Hungarian group confirmed that KYNA protects against LPS-induced sepsis in subsequent publications, in which a much lower KYNA dose of 30 mg/kg, i.p., was used [ 99 , 100 ]. Most recently, Wang et al (2022) demonstrated that intraperitoneally administered KYNA (5 mg/kg; three times at days 3, 6, and 9) reduced the mortality of mice infected with Candida albicans [ 94 ].…”
Section: Kynurenic Acid Supplementationmentioning
confidence: 99%
“…Detailed data on the health-promoting effects of KYNA administration in animals regardless of the route of administration are presented in Table S7 [ 26 , 87 , 90 , 93 , 94 , 95 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 , 123 ].…”
Section: Kynurenic Acid Supplementationmentioning
confidence: 99%
“…Norman et al ( 32 ) reported that neutrophils were significantly recruited by the brain during the acute inflammatory phase of sepsis, and the transmigration of neutrophils across the endothelial barrier was the main cause of vascular barrier breakdown. Recent studies documented that SB225002 (the antagonist of CXCR2) or kynurenic acid could protect the brain against neutrophil activation and BBB permeability changes in septic animals ( 33 , 34 ). However, neutrophil recruitment was not involved in cognitive impairment ( 35 ).…”
Section: The Immune Response Of Cns In the Development Of Saementioning
confidence: 99%